2021
DOI: 10.1177/24705470211014210
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of ketamine’s antidepressant effect: a clinical review of genetics, functional connectivity, and neurophysiology

Abstract: Major depressive disorder (MDD) is one of the leading causes of morbidity and all-cause mortality (including suicide) worldwide, and, unfortunately, first-line monoaminergic antidepressants and evidence-based psychotherapies are not effective for all patients. Subanesthetic doses of the N-methyl-D-aspartate receptor antagonists and glutamate modulators ketamine and S-ketamine have rapid and robust antidepressant efficacy in such treatment-resistant depressed patients (TRD). Yet, as with all antidepressant trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…Another notable effect of RSS was an increase in prefrontal gamma power that was greater in the responders than in the nonresponders. The use of gamma activity as a biomarker of treatment response in depression is an emerging topic [23,57,58]. It has been shown that different classes of antidepressant drugs have distinct effects on gamma oscillations, whereby serotonin-boosting antidepressants (e.g., citalopram and fluoxetine) suppress gamma, while noradrenergic drugs and ketamine increase gamma activity [59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Another notable effect of RSS was an increase in prefrontal gamma power that was greater in the responders than in the nonresponders. The use of gamma activity as a biomarker of treatment response in depression is an emerging topic [23,57,58]. It has been shown that different classes of antidepressant drugs have distinct effects on gamma oscillations, whereby serotonin-boosting antidepressants (e.g., citalopram and fluoxetine) suppress gamma, while noradrenergic drugs and ketamine increase gamma activity [59][60][61][62][63][64].…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature reviews in the field of glutamatergic ICNs support the notion that glutamate-based therapies act on several brain networks, leading to a rapid antidepressant response ( 38 , 326 , 327 ). As discussed by Alario and Niciu ( 326 ), further research exploring how glutamate-based therapies for depression, such as ketamine, have long-lasting effects with short-term connectivity changes is needed.…”
Section: Future Directions For Glutamate-based Therapeuticsmentioning
confidence: 98%
“…Existing literature reviews in the field of glutamatergic ICNs support the notion that glutamate-based therapies act on several brain networks, leading to a rapid antidepressant response ( 38 , 326 , 327 ). As discussed by Alario and Niciu ( 326 ), further research exploring how glutamate-based therapies for depression, such as ketamine, have long-lasting effects with short-term connectivity changes is needed. The promising findings that exist to date suggest the importance of coordinating the timing of study and neuroimaging procedures in a way that is physiologically appropriate to capture acute vs. delayed effects of glutamate-based therapies within affected ICNs ( 326 ).…”
Section: Future Directions For Glutamate-based Therapeuticsmentioning
confidence: 98%
See 1 more Smart Citation
“…One of the relevant impacts of ketamine's AMPA stimulation, the downstream enhancement of neurotropic factors such as BDNF and the resulting synaptogenesis, is a normalization of connectivity within and between multiple brain areas. For example, there is evidence that in certain conditions, with appropriate ketamine dosage, and at certain times post-treatment remitters showed temporary normalization ( 106 ) in global brain connectivity (GBC) between salience networks and the default mode network (DMN) ( 85 ); and between the dorsal caudate and the ventrolateral PFC ( 18 ); normalized connectivity between the amygdala and the subgenual anterior cingulate cortex (sgACC) ( 107 ); between the posterior cingulate and the right posterior insula; between left and right primary somatosensory cortex, between left frontal cortex and left primary somatosensory cortex ( 108 ), and between anterior insula to anterior cingulate ( 109 ); normalized global grain connectivity with global signal regression (GBCr) in the PFC ( 110 ), cerebellum, caudate, and insula ( 111 ); normalized connectivity in the sensorimotor and salience networks ( 112 ), in the parahippocampal gyrus, cingulate gyri, left medial and middle frontal gyri, and precuneus ( 113 ), in the right caudate ( 114 ), and in the sgACC ( 115 ).…”
Section: Therapeutic Effects Of Ketaminementioning
confidence: 99%